REDESIGNING GENERAL ENGLISH I SYLLABUS FOR INTENSIVE LANGUAGE PROGRAM - Prayogo, Agus; Rukmini, Dwi; Linggar Bharati, Dwi Anggani (English Education Journal, 2013)
The objectives of this study are: 1) to describe the current General English I syllabus coverage, 2) to find out the IAIN Walisongo studentâs needs in General English I. 3) to explain the redesigning processes of the syllabus of General English I, and 4) to explain how suitable is the redesigned syllabus of General English I to IAIN Walisongo students. The study conducted was research and development (R&D) which consists of seven stages to redesign the syllabus. The instruments used to gather the data use questionnaire, interview, observation, and test. The subjects of the study were 68 students. The findings show that the current syllabus of General English I is an integrated course that is mainly about reading and grammar. The studentsâ needs deal with the materials and activity that can support them to practice and communicate as well as TOEFL materials. The redesigning syllabus employs systematic procedures including current syllabus, studentsâ needs, and institution policy that were needed to be considered in determining syllabus components. The syllabus suitability was justified based on five aspects namely lecturerâs ability to develop the syllabus, adult learning characteristics covered in teaching learning activities, characters classification, syllabus practicality, and competence achieved.